EFEK JENIS MULSA DAN MACAM PUPUK TERHADAP PERTUMBUHAN DAN PRODUKSI KACANG PANJANG (VIGNA SINENSIS .L) VARIETAS PERSADA-355 - Nunuk Helilusiatiningsih; Rindi Arrozaki; Nur Fitriyah (BUANA SAINS, 2022)
The research aimed to study the interaction between the effects of various types of mulch and fertilizers on the growth and production of long beans. The research used a randomized block design, Factor I type of mulch consisting of 3 levels: M0 = No mulch, M1 = black and silver plastic mulch, and M2 = Straw mulch. Factor II is the type of fertilizer: including P1 = NPK Mutiara 600 kg/ha, P2 = biological Petrobio 90 kg/ha, P3 = NPK Mutiara 50% + biological Petrobio 50%. The results showed the effects of various types of mulch and fertilizers have significant interaction between the growth of leaf number and fruit weight of long beans, namely M1P3 (black silver mulch and application of 50% pearl fertilizer and 50% biological Petrobio).